Adaptive mechanisms of homeostasis disorders - Anna Maria Dobosiewicz; Daria Braun; Kamila Kromrych; Hubert Puszcz; Kalina Ziółkowska; Maja Kozłowska (Kazimierz Wielki University, 2017)
The ability to preserve a permanent level of internal environment in a human organism, against internal and external factors, which could breach the consistency, can be define as homeostasis. Scientific proven influence on the homeostasis has the periodicity of biological processes, which is also called circadian rhythm. The effect of circadian rhythm is also to see in the functioning of autonomic nervous system and cardiovascular system. Sleep deprivation is an example of how the disorders in circadian rhythm could have the influence on the homeostasis.